Gangguan Tidur Pada Pasien Kanker Payudara: Analisis Konsep dengan Pendekatan Walker dan Avant - Nur Aini; Fitria Endah Janitra; Anggi Lukman Wicaksana; Dang Thi Thuy My; Nguyen Van Trung (Faculty of Nursing Universitas Padjadjaran, 2022)
Background: Sleep disorders are a long-term issue for breast cancer survivors (BCS). Sleep disorders are among the top five most bothersome lasting difficulties in BCS, and they have a greater risk of sleep disorders than healthy persons and other cancer patients. Failure to understand sleep disorders in breast cancer patients causes nurses to be unable to give interventions appropriately.Purpose: To clarify the definition of sleep disorders in breast cancer survivors.Method: We comprehensively searched electronic databases from CINAHL, PubMed, and Ovid-MEDLINE. We used the eight steps from Walker and Avant to conduct a concept analysis. This approach was chosen because it gives a philosophical understanding of the concept using linguistic philosophy techniques. Model case and other cases were provided to give a conceptual definition of sleep disorders.Results: Finally, 62 studies were included. We found five antecedents of sleep disorder in breast cancer patients: psychological and emotional stress, physical symptoms, cancer treatment, lack of social support, and sociodemographic factors. This study found four common attributes of sleep disorders 1). abnormal sleep pattern, 2). troubling complaint, 3). persistent complaint, and 4). sleep difficulty. Finally, we found a reduction in quality of life as consequence of sleep disorder in breast cancer patients.Conclusion: Sleep disorders in breast cancer need attention and must be integrated into regular palliative care practices.